Music training is related to late ERP modulation and enhanced performance during Simon task but not Stroop task - Velasquez, Miguel A.; Winston, Jenna L.; Sur, Sandeepa; Yurgil, Kate; Upman, Anna E.; Wroblewski, Stella R.; Huddle, Annabelle; Colombo, Paul J. (Frontiers in Human Neuroscience, 2024)
Increasing evidence suggests that music training correlates with better performance in tasks measuring executive function components including inhibitory control, working memory and selective attention. The Stroop and Simon tasks measure responses to congruent and incongruent information reflecting cognitive conflict resolution. However, there are more reports of a music-training advantage in the Simon than the Stroop task. Reports indicate that these tasks may differ in the timing of conflict resolution: the Stroop task might involve early sensory stage conflict resolution, while the Simon task may do so at a later motor output planning stage. We hypothesize that musical experience relates to conflict resolution at the late motor output stage rather than the early sensory stage. Behavioral responses, and event-related potentials (ERP) were measured in participants with varying musical experience during these tasks. It was hypothesized that musical experience correlates with better performance in the Simon but not the Stroop task, reflected in ERP components in the later stage of motor output processing in the Simon task. Participants were classified into high- and low-music training groups based on the Goldsmith Musical Sophistication Index. Electrical brain activity was recorded while they completed visual Stroop and Simon tasks. The high-music training group outperformed the low-music training group on the Simon, but not the Stroop task. Mean amplitude difference (incongruent – congruent trials) was greater for the high-music training group at N100 for midline central (Cz) and posterior (Pz) sites in the Simon task and midline central (Cz) and frontal (Fz) sites in the Stroop task, and at N450 at Cz and Pz in the Simon task. N450 difference peaks occurred earlier in the high-music training group at Pz. Differences between the groups at N100 indicate that music training may be related to better sensory discrimination. These differences were not related to better behavioral performance. Differences in N450 responses between the groups, particularly in regions encompassing the motor and parietal cortices, suggest a role of music training in action selection during response conflict situations. Overall, this supports the hypothesis that music training selectively enhances cognitive conflict resolution during late motor output planning stages.